Positive bending capacity prediction of composite girders based on elastoplastic cross-sectional analysis. (15th July 2018) - Yang, Fei; Liu, Yuqing; Xin, Haohui
Highlights: The moment capacity of composite plate girders under positive bending is examined. Nearly 8000 composite sections are investigated. The yield strength of steel girder has an apparent effect on the bending capacity ratio. The bending capacity prediction equations of composite plate girders are proposed. Abstract: This paper investigates the positive bending moment capacity of composite plate girders with various geometric parameters as well as a wide range of concrete slab strengths and steel girder strengths. The elastoplastic cross-sectional analysis method is adopted to efficiently evaluate the positive bending capacity of the composite girder. The constitutive model of the steel girder is specified by a trilinear stress–strain relationship incorporating the strain hardening effect while the concrete slab based on the parabola-rectangle model. A large number of composite sections, which could represent the conventional cross-section of composite plate girders with medium spans, are designed along with various combinations of material strengths. For each composite section, its actual ultimate bending capacity and rigid plastic bending capacity are calculated and compared mutually. The analysis results indicate that the position of the plastic neutral axis has a significant effect on the ratio of the ultimate bending capacity to the rigid plastic bending capacity. The lower position of the plastic neutral axis locates, the more overestimate of the rigid plastic analysis method to predict the ultimate bending capacity. Besides, the yield strength of the steel girder also has an apparent effect on the ratio, of which the higher yield strength of the steel girder could lead to a lower ratio, while the concrete slab compressive strength has less influence on the ratio. The equation of predicting the ultimate bending capacity of the composite plate girder is proposed, in which a bending capacity reduction factor is introduced depending on the strength grade of the steel girder.